The effects of spatial representation on memory for verbal navigation instructions - Barshi, Immanuel; Healy, Alice F. (Memory & cognition, 2011)
Three experiments investigated effects of mental spatial representation on memory for verbal navigation instructions. The navigation instructions referred to a grid of stacked matrices displayed on a computer screen or on paper, with or without depth cues, and presented as two-dimensional diagrams or a three-dimensional physical model. Experimental instructions either did or did not promote a three-dimensional mental representation of the space. Subjects heard navigation instructions, immediately repeated them, and then followed them manually on the grid. In all display and experimental instruction conditions, memory for the navigation instructions was reduced when the task required mentally representing a three-dimensional space, with movements across multiple matrices, as compared with a two-dimensional space, with movements within a single matrix, even though the words in the navigation instructions were identical in all cases. The findings demonstrate that the mental representation of the space influences immediate verbatim memory for navigation instructions.